Indonesian Version of the Anterior Cruciate Ligament-Return to Sport After Injury Questionnaire Through Cross-Cultural Adaptation, Validity, and Reliability Testing - Muammar Ihsan; Ari Wibawa; I Made Muliarta; Ni Wayan Tianing (Universitas Udayana dan Diaspora Taipei Medical University, 2022)
Background: This study aimed to produce the Indonesian version of the Anterior Cruciate Ligament-Return to Sport After Injury (ACL-RSI) questionnaire and determine the value of content validity, construct validity, known-groups validity, and internal consistency reliability. Methods: First, the ACL-RSI questionnaire was translated through a cross-cultural adaptation process. Six experts in related fields assessed the adapted questionnaire by giving scores on four criteria: relevance, clarity, simplicity, and ambiguity, which will be calculated into content validity value. Seventy-one participants who experienced ACL injury because of sporting activities and had undergone reconstruction who joined the online community for Knee Injury Patients Support Group filled out the ACL-RSI to determine the known-groups validity and internal consistency reliability. The participants also filled out the Indonesian version of the Knee Injury and Osteoarthritis Outcome Score (KOOS) as a comparison to test construct validity. Results: The calculated content validity value obtained from the experts’ scoring was S-CVI/Ave = 0.97. Construct validity between ACL-RSI and all KOOS subscales showed a strong positive correlation with r = 0.78-0.87. Two hypotheses for known-groups validity were proven, with the group that had returned to their specific sport having a better ACL-RSI score than the group that had not returned (70.2 ± 10.0 vs. 49.3 ± 18.8, p<0.001), and the group planned to return to their specific sport as before the injury had a better ACL-RSI score than the group who did not intend to return (60.3 ± 16.5 vs. 32.6 ± 2.4, p<0.001). Internal consistency ACL-RSI showed very good reliability with Cronbach’s alpha = 0.96. Conclusions: The Indonesian version of ACL-RSI is valid and reliable for evaluating psychological readiness to return to sports after ACL reconstruction. However, a seemingly further similar study is necessary to fix the weaknesses in this study to produce a more representative Indonesian version of the ACL-RSI questionnaire.